2011
DOI: 10.1177/156482651103200304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Median Urinary Iodine Concentration as an Indicator of Iodine Status among Pregnant Women, School-Age Children, and Nonpregnant Women

Abstract: Comparison of median urinary iodine concentration as an indicator of iodine status among pregnant womenResults. There were 48 survey pairs with pregnant women and school-age children (total sample sizes of 8,622 and 16,844, respectively), and 26 pairs with pregnant and nonpregnant women (sample sizes of 3,222 and 5,520, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 19 publications
5
49
0
2
Order By: Relevance
“…It should be noted that most of these countries with concordant results between pregnant women and the general population adopted salt iodization programmes a long time ago (Switzerland in 1922, USA in 1924, Bulgaria in 1958) (37) . In a recent literature review on iodine status which included surveys that took into account -as well as pregnant women and school-aged children -also pregnant women v. non-pregnant women, Wong et al came to the conclusion that the iodine status of pregnant women has to be addressed by considering pregnant women separately (38) .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that most of these countries with concordant results between pregnant women and the general population adopted salt iodization programmes a long time ago (Switzerland in 1922, USA in 1924, Bulgaria in 1958) (37) . In a recent literature review on iodine status which included surveys that took into account -as well as pregnant women and school-aged children -also pregnant women v. non-pregnant women, Wong et al came to the conclusion that the iodine status of pregnant women has to be addressed by considering pregnant women separately (38) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been discussed if urinary iodine excretion in nonpregnant adults and in schoolchildren is useful for the evaluation of iodine status in pregnant women living in the same area [19]. In our Danish study, we found no difference between the median UIC in pregnant women, their male partners and children when urine sampling was performed at home under similar conditions (fig.…”
Section: Methods To Evaluate Id In Pregnant Womenmentioning
confidence: 53%
“…Based on median UIC, pregnant women were iodine sufficient but children had more-than-adequate iodine intake. A recent review concluded that when the median UIC in SAC or non-pregnant women indicated iodine intake was adequate or above requirements in a region, about half the time pregnant women in that same region had inadequate iodine intake (15) . Multiple studies have reported that when SAC have adequate iodine status (median UIC = 100-199 µg/l), pregnant women are deficient (median UIC < 150 µg/l), and that iodine sufficiency in pregnancy is attained only when the SAC have more-than-adequate (median UIC = 200-299 µg/l) iodine status (14,15,(25)(26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review concluded that when the median UIC in SAC or non-pregnant women indicated iodine intake was adequate or above requirements in a region, about half the time pregnant women in that same region had inadequate iodine intake (15) . Multiple studies have reported that when SAC have adequate iodine status (median UIC = 100-199 µg/l), pregnant women are deficient (median UIC < 150 µg/l), and that iodine sufficiency in pregnancy is attained only when the SAC have more-than-adequate (median UIC = 200-299 µg/l) iodine status (14,15,(25)(26)(27)(28) . In an earlier Thai study using similar methodology (25) but in families where not all meals were consumed within the household, despite a median UIC of 200 μg/l in SAC, iodine intakes in pregnant women were inadequate, with a median UIC of only 108 μg/l.…”
Section: Discussionmentioning
confidence: 99%